(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The linguoculturological aspects of folklore texts are examined in this abstract, with an emphasis on English tales as main examples. This study attempts to identify the distinctive linguistic and cultural traits that define the folklore genre by examining the language and cultural components found in these stories. This research provides important insights into the ways in which language and culture interact to shape folklore narratives by illuminating the intersections between language and culture within the framework of folklore through a combination of linguistic analysis and cultural interpretation. The results of this study emphasise the value of linguoculturological analysis in the study of traditional storytelling and advance our understanding of the complex interrelationships between language, culture, and folklore.